GROWTH AND PRODUCTION OF KATE'S ELEPHANT GRASS (Pennisetum purpureum cv. Mott) FERTILIZED WITH ORGANIC FERTILIZER DRAGONS FRUIT WASTE WITH DIFFERENT DECOMPOSITION TIMES - A., Fauzi; Witariadi, N. M.; Wirawan, I W. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the growth and yield of kate elephant grass ( Pennisetum purpureum cv. Mott) given organic fertilizer of dragon fruit waste with different decomposition times. The study was conducted at the Greenhouse, Research Station of the Faculty of Animal Husbandry, Udayana University Jalan Raya Sesetan Gang Markisa South Denpasar which lasted for 3 months, using a completely randomized design (CRD) with 6 treatments and 5 replications, so there were 30 experimental units. The decomposition time treatments were W0: 0 weeks; W1: 1 week; W2: 2 weeks; W3: 3 weeks; W4: 4 weeks and W: 5 weeks. The observed variables included growth, yield, and plant characteristics. The results showed that the application of dragon fruit waste organic fertilizer at the 1-week decomposition time (W1) was able to increase the variable number of tillers, while the variable plant height and number of leaves showed no significant difference, as well as the variable dry weight of leaves, dry weight of stems, root dry weight and total dry weight of forage gave no signi?cantly different results. The application of organic fertilizer of dragon fruit waste, on the variable of growth characteristics was able to increase the variable leaf area per pot, while the ratio of leaf dry weight to stem dry weight and the ratio of total dry weight of forage to root dry weight showed no significant difference. It can be concluded that kate elephant grass ( Pennisetum purpureum cv. Mott) which was fertilized with dragon fruit waste organic fertilizer was able to increase the growth and yield of kate elephant grass and at 1 week decomposition (W1) showed the best results in increasing the growth and yield of kate elephant grass ( Pennisetum purpureum cv. Mott).   Keywords: decomposition, yield, organic dragon fruit waste, Pennisetum purpureum cv. Mott, growth fertilizer